Al AL-MASYAQQĀH TAJLIB AL-TAYSIR TERHADAP PEMIKIRAN DAN PERILAKU EKONOMI MASYARAKAT DI ERA REVOLUSI INDUSTRI 4.0 - hisam ahyani (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2022)
The Qawa'id fiqhiyyah al-Masyaqqāh Tajlib al-Taysir is a general foundation in social thinking and behavior that provides guidance for all people and nations in Indonesia, especially in the Era of the Industrial Revolution 4.0 as it is today, to carry out various interactions with each other. The guidance given concerns several aspects of life such as legal, economic, social, political and state aspects, as well as culture to human behavior problems when collided with Islamic economics by understanding the principles contained therein. This research focuses on the study of qawa'id Fiqhiyah al-Masyaqqāh Tajlib al-Taysir, which means Difficulty of Giving Birth to Ease, and its implications for economic thought and behavior in society in the current era, namely the era of the Industrial Revolution 4.0. In this case, the understanding of the difficulty of giving birth to ease is that mutlaq is needed to carry out an ijtihad or renewal of thought. The existence of this fiqh principle, in which the difficulty of giving birth to convenience proves that Islam, with all its tools, pays close attention to human behavior in fulfilling the daily needs of both social and economic needs. This can be proven when Allah SWT allows Muslims to interact and transact with non-Muslims at the same time, even Allah SWT gives flexibility to the mukalaf in determining their economic activities according to their ability levels. However, this almost Qath'i rule, namely masyaqqah is limited by the Shari'a in order to maintain the originality of human benefit from the rules made by the creator